EVOLUCIÓN CLÍNICA DE LOS PACIENTES CON DIABETES MELLITUS SOMETIDOS A ANGIOPLASTÍA CORONARIA CON IMPLANTACIÓN DE STENT DE ENERO A DICIEMBRE DEL 2009 EN EL HOSPITAL SAN JUAN DE DIOS - Monge Ortega, Patricia (2011)
Background: Percutaneous coronary angioplasty(PTCA) with stent placement is both safe and effective interventional treatment for ischemicheart disease. This disease has a high prevalenceand impact in the morbidity and mortality in the general population. The purpose of this study is to describe the outcomes obtained with PTCA/stent terapy at the San Juan de Dios Hospital during the period between January 2009 and December 2009. Methodology: A descriptive, retrospective and observational study was performed by collecting information from medical files of 268 patient streated with PTCA during the study period. Ananalysis of the outcomes was performed on those patients that met inclusion criteria. Results: We included 88 diabetic patients (62 males and 26 females). 18,3% of the patients haddyslipidemia, 49,8% were smokers and 87,5%had hypertension. In relation with previous procedures, 12,5% of the patients had one previous angioplasty and 2,3% had bypasssurgery. On average there were 1,4 ± 0,6 vessel streated, with a minimum of 1 vessel and amaximum of 3 vessels. On average there were 1,7 ± 1,0 stents perpatient, with a minimum of one and a maximumof five stents. The number of stents per treatedvessel was 1,3. Medicated stents were used in 89,4% of the cases. Succesful PTCA accountedfor 96,6% of the individuals (85 cases), and only6 patients (6,8%) had procedure related complications. Major cardiovascular events after PTCA ocurredun 23 patients (26,1%). Twentythree patients(26,1%) had major cardiovascular events after PTCA, and 39,1% of these, required another PTCA. There were two patients who were tratedfor two different lesions (9,33%) and 4,5% of the patients had reestenosis. A 3,4% (3 cases) dieafter the procedure due to cardiovascular causes (two cases because of cardiogenic shock and onecase because of advanced coronary arterydisease). The first two died during the firstmonth after the procedure and the other one die done year after the angioplastic procedure. Conclusion: Diabetic patients had higher risk ofthrombosis, restenosis, reintervention and overallmortality on both groups of stents.